CLIMATE, TROPICALITY OF THE BRAZILIAN CENTRAL PLATEAU, AND TUBERCULOSIS LOAD - Brandao, Erlayne; Borsato, Victor da Assunção; Steinke, Ercília Torres; Evangelista, Maria do Socorro Nantua (Mercator; Vol 22 (2023)DO - 10.4215/rm2023.e22026, 2023)
The current literature has pointed out an influence of climatic and environmental aspects on tuberculosis (TB) burden. Among the main influences, the effects of climate stand out. The present study aims to identify whether the tropicality of the Brazilian Central Plateau increases TB burden in the Federal District, Brazil. This is an ecological study carried out with 1,291 new TB cases notified to the Notifiable Diseases Information System of the State Health Department of the Federal District. We studied the participation of air masses and the cases of tuberculosis during the summers from 2006 to 2017. For the rhythmic analysis, we considered the summer of 2006, as it was the year with the highest frequency of TB cases. We used Pearson's correlation test. The most frequent types in the summers were the continental Equatorial mass, with a 77.5% frequency, and the Atlantic Tropical mass, 13.8%. We observed no correlation between the performance of atmospheric systems and TB cases; that is, meterological variables showed no contribution to the greater burden of TB in the Federal District. Keywords : Tuberculosis. Climate. Air Masses. Climate Changes. Effects of Climate Change.